Structure and properties of cerium phosphate and silicophosphate glasses - Xia, Yang; Calahoo, Courtney; Rodrigues, Bruno Poletto; Griebenow, Kristin; Graewe, Lennart; Wondraczek, Lothar (Journal of the American Ceramic Society, 2023)
We report on the fabrication, properties, and structure of cerium pyrophosphate glasses and partially substituted cerium silicophosphates. In those glasses, cerium occurs predominantly as Ce(III). A combination of dynamic nuclear magnetic resonance and electrical impedance spectroscopy is used to overcome the problem of assessing cerium speciation. While optical spectroscopy is unable to quantify the ratio of Ce(III)/Ce(IV) due to spectral overlap, proxy observations of the effect of silica-for-cerium substitution on optical extinction and the shape and width of the UV band gap corroborate vibrational spectroscopic data of the structural roles of cerium and silica. While silica bonding to phosphate units appears to stabilize Ce(IV), it also impedes the polaron transport, leading to higher polaron activation energy and lower electronic conductivity. On the other hand, Ce(III) is stabilized by coordinating to P = O.
CRIS-Team Scopus Importer:2023-04-20
Keywords: cerium speciation; phosphate glasses; polaron conductivity; structure–property relations